(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The owners also resort and fraudulent model to deployment the ranking of the apps in the popularity list. There is limited understanding in the evolvement though the prevention of fraud has been widely is finding. We implement Firefox users to the number of installed applications on their Facebook profiles. We present the temporal analysis of the Facebook applications’ stating and removal dataset take user requirements. Online social networks (OSNs) are new vectors for cybercrime and hackers are finding new ways. We present results in the perspective of over 12K users to install. Our purpose system is creating a Facebook application and user goal is to develop a FRAppE Face book’s Rigorous Application. Online Social Networks (OSN) takes third party apps to changes the user experience on the platforms. Such modifications are interesting communicating number of online friends and new models such as playing games. We take facebook provides to developers an API that facilities app applied into Facebook user experience. Present Ackers to started taking advantage of the resource of this third-party apps platform and deploying small applications and small apps will give a profitable business for hackers given the recognition of OSNs. It is safe and secure data is added in our wall. Thus, the Offensive words and posts are blocked with the help of dictionary using filters and it is not publicly posted to user wall.